Media and subnational democracy: the case of Bahia, Brazil. Issue 1 (2nd January 2017) - Durazo Herrmann, Julián
ABSTRACT: It is a well-known fact that the transition to and consolidation of democracy in Latin America have been problematic, especially at the subnational level. It is also commonplace to equate an independent media system with a strong democracy. While each of these fields has witnessed important developments in the last decade or so, there have been sparse attempts to draw the theoretical links between them. In this article, I argue that there are important insights to be gained from such an endeavour. Bahia, a state in north-eastern Brazil, is an ideal case study to bring these perspectives together. This study offers fresh insights on state–society relations at the subnational level and on the contemporary interaction between the public and the private spheres in Latin America. Last but not least, it will also provide a better grasp on the challenges democratization faces at the subnational level and the role of the media in them.